Psychological intervention in the school: Between social mandate and commission - Pagano, Paola; DI Ruzza, Federica (Quaderni di Psicologia Clinica, 2015)
The article proposes a reflection on the activation of a psychological function, by reporting two experiences of psychological intervention in school context of Southern Italy and Central. The first experience is aimed at preventing school drop out and social discrimination. The psychologist intervenes in a school, located in a neighborhood at risk of social exclusion, which has difficulties understanding families’ and students’ demand. The second experience concerns a project of work-related learning in a secondary school. Here, the psychologist intervenes within an individualistic school culture where, by using labels as “youth” and “adolescent”, the school loses sight of the relationship between students and school context and the students’ learning demand. These experiences arise from the social mandate derived from public calls for proposal by the Apulia Region, with the programme “Rights at school”, and the Ministry of Education, Universities and Research (MIUR). In both cases the psychologists don’t undertake the mandate as it is, but they take the opportunity to intervene offered by the mandate, to build with the school the commission of intervention and negotiate the respective functions, without losing out the calls’ purposes.